Thyroid-like follicular carcinoma of kidney - Chandranshu Tripathi; Naveen Kumar Gupta; Dilip Kumar Pal (Annals of Medical Science and Research)
Renal cancer resembling thyroid-like tumor of the kidney is extremely rare. This type of renal tumor shows the morphologic features that resemble follicular carcinoma of thyroid. In our case, a 62-year-male patient presented with flank pain with all blood parameters in normal range. Chest X-ray were normal, contrast enhanced computed tomography report showed well defined hyperdense lesion of size 26 mm × 21 mm showing homogenous enhancement (hu 46–126 from pre to post contrast) noted in lower pole of right kidney. Patient underwent radical nephrectomy, histopathological examination suggestive of thyroid-like follicular carcinoma with IHC markers as TTF1-negative, CK7-negative, and PAX8-negative. Patient was referred to Department of Radiotherapy for further management. Immunohistochemical staining studies in the literatures showed that this tumor consistently expressed the transcription factor PAX-8 but did not express the thyroid-specific antibodies TG and TTF-1. Most tumors with diameters of more than 4 cm or associated with invasive growth or distant metastasis are treated mainly with radical nephrectomy, combined with the corresponding regional lymph node dissection. Surgical treatment is still the preferred therapeutic method. The disease seems to have a good prognosis.